Problems and prospects of the Russian Federation customs authorities digitalisation - I. A. Aksenov (Вестник университета, 2022)
Digital technologies are becoming an integral part of the modern society. They penetrate into all spheres of life and activity of mankind. Customs is no exception. The purpose of the study is to identify the problems and prospects for the introduction of digital technologies in the activities of the customs authorities of the Russian Federation. The methodological basis of the study is a set of measures of scientific knowledge, including general scientific methods of analysis, synthesis, induction and deduction, as well as private scientific methods: system analysis, logical method. The study argues that customs operations are directly related to the extent to which digital technologies are developed and implemented in the activities of customs authorities. Despite all the obvious prospects for further digitalisation in the field of customs, there are certain problems. In the article, the author identifies the key issues of the Russian Federation customs authorities digitalisation. Based on the identified limitations, recommendations are made for their elimination, taking into account the current economic and geopolitical situation.